Epiphytic macrolichen communities take decades to recover after high‐severity wildfire in chaparral shrublands. (10th May 2021) - Miller, Jesse E. D.; Weill, Alexandra M.; Villella, John
Abstract: Aim: Fire regimes are shifting globally due to climate change, land management practices and population growth, putting species at risk if they are unable to adapt to more frequent or severe wildfires. While many fire‐adapted species may be able to accommodate some amount of change in fire regimes, fire‐sensitive or late‐successional species that colonize fire‐prone ecosystems between wildfires may be especially vulnerable to more frequent or severe fires. Here, we seek to understand the rate of lichen recolonization after high‐severity fires in an ecosystem that is experiencing increasing fire frequency. Location: The Inner North Coast Range of California, USA. Methods: Using a chronosequence of wildfires in a Northern California chaparral shrubland, we compare lichen communities among sites that burned 3, 13, 22, 30 and 65 years previously, as well as old‐growth chaparral sites without a recorded fire over the past century. Results: We find that lichen richness increases consistently with time since fire but begins to level off 20–30 years following fire, roughly corresponding to the closure of the shrub canopy. Some taxa and guilds were found only in old‐growth chaparral. Conclusions: Our findings highlight that fire‐intolerant organisms may be relatively slow to recolonize landscapes after high‐severity fire and that the majority of chaparral lichen taxa may be lost where fire intervals shorten to <20 years, which has already occurred in some parts of California.